Trends in elasmobranch feeding ecology studies - Hugo Bornatowsk; Maiara A. Hayata; Renato H. A. Freitas (Ocean and Coastal Research)
Reviews can be useful to provide an overview of specific knowledge areas to facilitate research guidelines and the comparison of study results. Therefore, we aimed to detect regions, environments, and taxonomic groups of elasmobranch that lack information on their feeding ecology and consequently need further attention. Using specific keywords on diet and feeding studies, we searched for articles on the trophic and feeding ecology of elasmobranchs. We found an increase in studies over the last 24 years, with an emphasis on stomach contents and stable isotopes. The USA, Australia, Mexico, Argentina, and Brazil were the countries with the highest number of published articles. Australia, the USA, Argentina, Brazil, Mexico, South Africa, Spain, Uruguay and India were the countries with the highest number of species studied. Estuarine and freshwater environments seem to need more attention, since studies on species in these environments were scarce (~3%). The total number of shark and ray species studied showed no significant differences (164 and 186, respectively), but most of the articles reviewed concerned sharks (67.5%). The larger elasmobranch families also need more attention, especially demersal species such as Rajidae, Dasyatidae, Arhynchobatidae, and Sycliorhinidae. Feeding studies only analyze some of the data deficient (